Legal Consequences for Perpetrators of Online Fraud Crimes on Electronic Social Media. - Mutiara Zahra, Andien; Pawennai, Mulyati; Faisal, Muhammad (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to find out and analyze the legal consequences for perpetrators of online fraud through electronic social media. To find out and analyze legal efforts for victims of online fraud on social media. This study uses an empirical legal research method by focusing on analyzing primary data and secondary data using qualitative data analysis techniques. The results of this study indicate that the legal consequences for perpetrators of online fraud through electronic social media. The application of legal sanctions for perpetrators of online investment fraud has not been expressly regulated in a special law that can provide criminal penalties for perpetrators but is regulated in the Criminal Code Article 372 with a maximum imprisonment of four years or a maximum fine of nine hundred rupiah, and Article 378 with a maximum imprisonment of 4 (four) years. Efforts to provide countermeasures in providing criminal policies are carried out with the criminalization aspect of criminal law, namely by forming special laws to regulate things that are prohibited in this case. Legal action is a solution provided by law to victims whose rights to justice are not fulfilled, as well as providing relief and peace of mind for the criminal acts that befell them. Online Fraud Actions involve the following steps such as Legal Efforts through Litigation, and Legal Efforts through Non-Litigation. This Research Recommendation Should be the Urgency of Making Regulations or Legal Arrangements for Investment or Commonly Called Online Capital Investment Specifically in Order to Provide Criminal Aggravation and Strengthen Criminal Sanctions for Online Fraud Perpetrators for the Purpose of the Law, namely Legal Certainty, Justice and Benefit. The State in Protecting Online Practices Should Make Regulations That Specifically and Firmly Regulate the Aspects of Investment Practices or Online Capital Investment in Order to Achieve Legal Certainty.